Avaliação das emissões conduzidas e radiadas geradas por unidade eletrocirúrgica e sistema de iluminação com lâmpadas fluorescentes em equipamentos médicos - Moraes, Fábio Brignol de (2013)
This work presents a study on electromagnetic interference radiated and conducted emissions generated by the lighting system and the electrosurgery unit (eletric scalpel) in na operating room of a hospital in Pato Branco / PR. The work consisted of measurements of conducted and radiated emission of fluorescent lighting systems in the laboratory of conducted and radiated “in loco” electrosurgery unit emissions. Futhermore, a study was made of references on standarts, national and international, that focus on these two systems. Because of the work, has an overview on the situation of conducted and radiated emissions, the fluorecent lighting used in electrosurgical unit and hospital systems.